After the Typhoon: Multicultural Archaeologies of World War II on Peleliu, Palau, Micronesia. Issue 3 (September 2013) - Price, Neil; Knecht, Rick; Ballinger, Steve; Cypra, Steve; Emesiochel, Calvin; Hesus, Tangie; Kloulechad, Errolflynn; Lindsay, Gavin; McQuillen, David; Ngirmang, Sunny Ochob
<x content-type="archive" xml:space="preserve">Abstract</x> In the autumn of 1944, one of the worst battles of the Pacific War took place between the Americans and Japanese on the small Micronesian island of Peleliu in the Palau group. Over more than two months of combat, its garrison fought almost literally to the last man, while US casualties were proportionately among the heaviest of the entire war. Afterwards largely overlooked in the public consciousness, the battlefield is now the best preserved of the Pacific theatre and is the subject of an extensive archaeological survey, coupled with a programme of large-scale unexploded ordnance removal. This paper is the second of two, following our previous publication summarizing the more conventional results of the fieldwork. Here, we instead explore the deeper ways in which the material culture of Peleliu can illuminate the multicultural histories of the fighting and thus enable the battlefield to stand as a lasting, reflective memorial to all those whose lives it touched. We address the neglected narratives of the Japanese, the Korean and Okinawan forced labourers, and also the marginalized members of the US forces including African-Americans, Hispanics, and Native Americans. In particular, we attempt to bring out the indigenous perspective on the material heritage of an imported and deeply alien war. In combination, we hope the research can provide new theoretical avenues of exploration for the archaeology of battlefields.